Application of biomaterials in experimentally induced alveolar bone osteoporosis - Ajduković Zorica R.; Mihailović Dragan S.; Najman Stevo J.; Savić Vojin P.; Aleksov Ljiljana; Stanković Saša; Krunić Nebojša; Ristić Kitka (Serbian Medical Society - Dental Section, Belgrade, 2003)
Rehabilitation of alveolar bone with tissue defect caused by advanced osteoporosis is a common problem in stomatology and maxillofacial surgery. One of therapeutic approaches is implantation of biomaterials. The aim of this study was to estimate biocompatibility, osteoconductive and reparative capabilities of biomaterials in wound healing of rats which are experimentally treated with corticosteroids during 12 weeks to produce osteoporosis. The syngenic Sprague Dolly female rats 6-8 weeks old were divided into the experimental and control groups. In the experimental group comprising 5 subgroups, the bone defects were made in the left mandible by 1.4 mm borer, in sterile conditions. In the first subgroup of rats healing wasspontaneous. In other four subgroups hydroxyapatite (HAp) composite, a mixture of HAp and autologous plasma, a mixture of HAp and fibrin glue, and glass jonomer bone cement were used, respectively. The best results were obtained with a mixture of HAp with plasma. Histologically, the new bone tissue was found in both spongious and compact mandibular parts. Our. results suggest that HAp can help in new bone tissue formation in animals treated with corticosteroids.